The Institutional Balance: a Janus-faced concept of EU constitutional law (Politeja, 2016)
The concept of institutional balance is an original theory associated with the development of the EU institutional structure. This article offers a critical analysis of the different uses of the concept. While doing that, the article provides representative samples of the ways in which the concept has been used in the processes of the European integration, including its practical implementation by the European Court of Justice. Our argument is that, in its current state, the concept of institutional balance serves both reactive and transformative functions within the EU law. It emphasises the necessity to periodically check and adjust the power distribution architecture in response to new challenges of the EU evolution process. Moreover, it serves as a conceptual vehicle through which different power configurations within the EU context may be both criticized and legitimized.